Amyotrophic lateral sclerosis weakens spinal recurrent inhibition and post-activation depression - (:unkn) unknown (ELSEVIER IRELAND LTD, 2020)
Objectives: Amyotrophic lateral sclerosis (ALS) disrupts motoneurons that control movement and some vital functions, however, exact details of the neuronal circuits involved in ALS have yet to be fully endorsed. To contribute to our understanding of the responsible neuronal circuits, we aimed to investigate the spinal recurrent inhibition (RI) and post-activation depression (P-AD) in ALS patients. Methods: In two groups of ALS patients, i.e. lumbar-affected (clinical signs in leg muscles) and nonlumbar-affected (clinical signs in arms or bulbar region but not in the legs), RI and P-AD on the soleus muscle were investigated using single motor units and amplitude changes of H-reflex in surface electromyography, respectively. The data were compared with healthy subjects. Results: Compared to controls, P-AD of H-reflex was reduced severely in lumbar-affected patients and reduced to a certain degree in nonlumbar-affected patients. Similarly, a significant reduction in the duration of RI on firing motoneurons was found in lumbar-affected patients (11.5 +/- 2.6 ms) but not in nonlumbar-affected patients (29.7 +/- 12.4 ms, P < 0.0001) compared to controls (30.8 +/- 7.2 ms, P < 0.0001). Conclusion: The current study revealed that spinal inhibitory circuits are impaired in ALS. Significance: These findings may provide insight for proposing new therapeutic approaches and following disease progression in humans. (c) 2020 International Federation of Clinical Neurophysiology. Published by Elsevier B.V. All rights reserved.
Keywords: Recurrent inhibition; Renshaw cells; Amyotrophic lateral sclerosis; Post-activation depression; Motoneuron